1997
DOI: 10.1079/pns19970058
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-hormone signals regulating muscle protein turnover in pigs

Abstract: In economic terms, muscle is the most important tissue for pig producers. Research has been largely focused, therefore, on the means by which to increase carcass muscle content, as well as the efficiency of nutrient use for muscle growth. Since a major component in this tissue is protein, the rate at which protein is continuously synthesized and degraded, i.e. the rate of protein turnover, is related to growth and, particularly, to feed efficiency for growth. Thus, protein turnover is of nutritional importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…In general, long term feeding of dietary proteins with a lower biological value leads to significant lower growth Performance, i.e. protein deposition, than feeding dietary proteins with a higher value (SALTER et al, 1990;ROY et al, 1997;SEVE et al, 1997). The present results indicate changes in the same manner when feeding SPI-with the lower biological value in comparison to CAS+ in all periods at both protein levels.…”
Section: Discussionsupporting
confidence: 74%
“…In general, long term feeding of dietary proteins with a lower biological value leads to significant lower growth Performance, i.e. protein deposition, than feeding dietary proteins with a higher value (SALTER et al, 1990;ROY et al, 1997;SEVE et al, 1997). The present results indicate changes in the same manner when feeding SPI-with the lower biological value in comparison to CAS+ in all periods at both protein levels.…”
Section: Discussionsupporting
confidence: 74%
“…This could be associated with a stimulation of the intestinal fractional protein synthesis rate (Sè ve et al, 1986;Ponter et al, 1994). In the same way, Sè ve and Ponter (1997) reported that an inadequate dietary threonine supply in early-weaned piglets induced an increased fractional protein synthesis rate in the duodenum probably associated with an acceleration of protein turnover.…”
Section: Discussionmentioning
confidence: 73%
“…This could be ascribed to an enhanced AA utilisation by the tissues of the LT piglets. Indeed, previous results showed that in weaned piglets, threonine deficiency increased fractional protein synthesis rate in the muscle and in the intestine (Sè ve and Ponter, 1997). Concerning non-essential AA, decrease in plasma glutamine and some of their end products (alanine, citrulline and ornithine) in LT piglets at day 4 could be in relation to the high energy cost of an increased protein turnover in the intestine since glutamine is used as a major energy fuel by the gut.…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown that postnatal application of somatotropin clearly stimulates muscle fibre hypertrophy in pigs (Beermann et al 1990;Solomon et al 1990;Lefaucheur et al 1992;Sørensen et al 1996) and other mammalian species (Ullmann and Oldfors 1989;Ono et al 1996), but does not affect the number of muscle fibres as described for pig muscle (Rehfeldt et al 1999). Muscle fibre hypertrophy as induced by exogenous growth hormone is based mainly on increased satellite cell proliferation and muscle protein synthesis (Beermann et al 1983;Etherton and Bauman 1998) and also decreased protein degradation (Weikard et al 1992;Sève and Ponter 1997).…”
Section: Introductionmentioning
confidence: 98%